A Generalization of Warped Product Manifolds with Spin(7) Holonomy - Bilge, Ayşe H.; Uǧuz, Selman; Fernandes, Rui Loja; Picken, Roger (AIP, 2008)
We define warped‐like product manifolds and prove that if M is a 3+3+2 warped‐like product manifold where the fibers are connected, simply connected and complete and if M has Spin(7) holonomy, then the fibers are isometric to S3. This work is an abbreviated version of the paper [Bilge, A. H., Uǧuz, S., Warped‐like products manifolds with Spin(7) holonomy, submitted for publication].